SERUM PROGESTERONE PROFILE DURING DIFFERENT STAGES . OF INDUCED AND NATURAL ESTROUS CYCLES IN BITCHES - BECHA, B BIBIN; GHOSH, N ARAVINDA (The Indian Journal of Animal Reproduction, 2023)
Estrus was induced in twelve anestrus bitches using a sustained release preparation of leuprolide acetateand diethylstilbestrol. Bitches with GnRH regimen of estrus induction (n=6) showed a mean serum progesteronelevel of 0. 72 ± 0.33 ng/ml on the first day of treatment, 0.28 :t: 0.08 ng/ml on the second day of proestrus, 3.80 ±1. 07 ng/ml on the first day of estrus, 15.12 ± 3. 73 ng/ml on the day of second mating and 17. 92 ± 1.15 ng/ml onthe tenth day of second mating. Bitches treated with diethylstilbestrol (n=6) showed a mean serum prog9Steroneprofile of0.47 ± 0.27 ng/ml on the first day of treatment, 0.2 ng/ml on the second day of proestrus, 5.53 ± 0.66 ng/ml on the first day of estrus, 13.67 ± 2.84 ng/ml on the day of second mating and 15.87 ± 0.27 ng/m1 on the tenthday of second mating. Animals in natural estrum (n=6) showed a mean serum progesterone level of 0.36 ± 0.12 ng/ml on the second day of proestrus, 3.56 ± 0.50 ng/ml on the first day of estrus, 8.12 ± 0.36 ng/ml on the day ofsecond mating and 17.80 ± 0.58 ng/ml on the tenth day of second mating. In treatment groups, the serumprogesterone levels raised quickly to higher levels during estrum when compared to control animals, but in allanimals it reached to similar levels by metestrum. Retrospective studies revealed that ovulation occurred in GnRHtreated and diethylstilbestrol treated animals by 8th to 11 111 day and 6th to 1111> day from first day of proestrusrespectively. Ovulation occurred in estrus induced animals earlier than that in control animals which is due to theshortened and pronounced proestral changes in treated animals. But in animals where estrus was induced usingdiethylstilbestrol, the ovulatory period was inconsistent which necessitates more frequent assessment ofprogesterone profile for timing of ovul_ation.1 GnRH treated animals, diethylstilbestrol treated animals and controlanimals had a conception rate of 83. 3, 50 and 83.3% respectively with similar gestation length and litter size in allgroups. It is concluded that serum progesterone profile studies can be employed for selecting good subjects forestrus induction treatment, timing of ovulation and to assess the normal progression of the estrous cycle in naturaland induced estrous cycles.
Keywords: Induction of estrus; Progesterone profile; Bitches